2021
DOI: 10.15586/aei.v49i3.181
|View full text |Cite
|
Sign up to set email alerts
|

Early life triggers for food allergy, that in turn impacts dietary habits in childhood

Abstract: Introduction and objectives: In order to investigate food allergy’s prevalence, risk factors and eating behavior of children with relevant anamnesis, a study was performed in Cypriot primary schools.Patients: A specially composed questionnaire for self-reported adverse reactions to food, cre-ated in the context of the EuroPrevall study, was distributed in 13 representative primary schools across the country. Participants were sub-grouped into three groups; healthy (H), those with unconfirmed food hypersensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Children who are pre- and postnatally exposed to tobacco smoke have a significantly higher risk of FA ( 65 ), and in our study maternal smoking was associated with FPIAP. Paternal smoking was equivalent in the two groups and had less effect, probably because fathers spend less time in close contact with the infants ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Children who are pre- and postnatally exposed to tobacco smoke have a significantly higher risk of FA ( 65 ), and in our study maternal smoking was associated with FPIAP. Paternal smoking was equivalent in the two groups and had less effect, probably because fathers spend less time in close contact with the infants ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Martin and colleagues showed that infants fed both breastmilk and formula at any point during the first 4 months were less likely to develop FPIAP than infants fed exclusively formula or exclusively breastmilk [ 4 ]. Even the presence of the infants in the kitchen during cooking appeared to exert a protective role [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This investigation was conducted in parallel with a survey on food-hypersensitivity in the pupils attending the schools under question. The age range of the schoolchildren in the study schools was 5.5-12 years (mean 8.7 ± 1.7 years) [3]. The school principal of each school, or a schoolteacher designated by the school principal as the most appropriate person to provide the required information on the school preparedness for FA was assigned to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Food allergy (FA) is a common pediatric emergency and constitutes a significant concern for the personnel of preschool facilities and schools. Its prevalence varies in different parts of the world, and in Europe it affects about 6% of primary school children [1][2][3]. Even when children with FA are trained to avoid the offending foods, accidental FA reactions may occur, about 18% of these at school [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation